2023
DOI: 10.3390/polym15020359
|View full text |Cite
|
Sign up to set email alerts
|

Selective Photocatalytic Reduction of Nitrobenzene to Aniline Using TiO2 Embedded in sPS Aerogel

Abstract: In recent years, aromatic substances have become the focus of environmental pollution-related concern due to their high stability and mutagenicity. In this regard, researchers have focused their attention on the development of photocatalytic processes to convert nitroaromatic compounds into aniline. In this work, the photocatalytic conversion of nitrobenzene (NB) to aniline (AN) was studied. The photocatalytic reaction was performed using commercial TiO2 (P25) and a photocatalytic aerogel, based on P25 embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In this regard, Navarra et al. prepared a monolithic aerogel based on commercial TiO 2 particles (P25) embedded in sPS (sPS/P25) for the photocatalytic conversion of nitrobenzene to aniline under UV light using ethanol as reducing agent [20a] . Photocatalytic tests showed that sPS/P25 aerogel composite was able to ensure the almost complete conversion of nitrobenzene and aniline yield higher than 99 % after 180 min of irradiation time [20a] …”
Section: Hydrophobic Polymer‐photocatalyst Compositesmentioning
confidence: 99%
“…In this regard, Navarra et al. prepared a monolithic aerogel based on commercial TiO 2 particles (P25) embedded in sPS (sPS/P25) for the photocatalytic conversion of nitrobenzene to aniline under UV light using ethanol as reducing agent [20a] . Photocatalytic tests showed that sPS/P25 aerogel composite was able to ensure the almost complete conversion of nitrobenzene and aniline yield higher than 99 % after 180 min of irradiation time [20a] …”
Section: Hydrophobic Polymer‐photocatalyst Compositesmentioning
confidence: 99%